2013
DOI: 10.1371/journal.pone.0064963
|View full text |Cite
|
Sign up to set email alerts
|

Elevational Distribution and Conservation Biogeography of Phanaeine Dung Beetles (Coleoptera: Scarabaeinae) in Bolivia

Abstract: Insect macroecology and conservation biogeography studies are disproportionately scarce, especially in the Neotropics. Dung beetles are an ideal focal taxon for biodiversity research and conservation. Using distribution and body size data on the ecologically important Phanaeini, the best-known Neotropical dung beetle tribe, we determined elevational patterns of species richness, endemism, body size, and elevational range in Bolivia, specifically testing Bergmann’s and Rapoport’s rule. Richness of all 39 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 78 publications
(132 reference statements)
7
34
7
Order By: Relevance
“…In the Andes in Ecuador, no significant change in FWLs was found for Geometridae (males) between 1000 and 2700 m a.s.l., with idiosyncratic results for subordinate taxa (Brehm and Fiedler 2004). In contrast to our results, Guevara and Avilés (2007) documented decreasing body sizes of several insect groups along an elevational gradient in Ecuador; Kubota et al (2007) found decreasing body sizes in tephretid flies with increasing elevation in Brazil; Dillon et al (2006) concluded that insects living at higher elevations do not tend to have larger body sizes; Herzog et al (2013) found decreasing body size patterns of phanaeine dung beetles in Bolivia with increasing elevation; and Hawkins and DeVries (1996) found that Costa Rican butterflies showed no general body size trends with elevation. In contrast to our results, Guevara and Avilés (2007) documented decreasing body sizes of several insect groups along an elevational gradient in Ecuador; Kubota et al (2007) found decreasing body sizes in tephretid flies with increasing elevation in Brazil; Dillon et al (2006) concluded that insects living at higher elevations do not tend to have larger body sizes; Herzog et al (2013) found decreasing body size patterns of phanaeine dung beetles in Bolivia with increasing elevation; and Hawkins and DeVries (1996) found that Costa Rican butterflies showed no general body size trends with elevation.…”
Section: Body Size Along the Elevational Gradientcontrasting
confidence: 85%
“…In the Andes in Ecuador, no significant change in FWLs was found for Geometridae (males) between 1000 and 2700 m a.s.l., with idiosyncratic results for subordinate taxa (Brehm and Fiedler 2004). In contrast to our results, Guevara and Avilés (2007) documented decreasing body sizes of several insect groups along an elevational gradient in Ecuador; Kubota et al (2007) found decreasing body sizes in tephretid flies with increasing elevation in Brazil; Dillon et al (2006) concluded that insects living at higher elevations do not tend to have larger body sizes; Herzog et al (2013) found decreasing body size patterns of phanaeine dung beetles in Bolivia with increasing elevation; and Hawkins and DeVries (1996) found that Costa Rican butterflies showed no general body size trends with elevation. In contrast to our results, Guevara and Avilés (2007) documented decreasing body sizes of several insect groups along an elevational gradient in Ecuador; Kubota et al (2007) found decreasing body sizes in tephretid flies with increasing elevation in Brazil; Dillon et al (2006) concluded that insects living at higher elevations do not tend to have larger body sizes; Herzog et al (2013) found decreasing body size patterns of phanaeine dung beetles in Bolivia with increasing elevation; and Hawkins and DeVries (1996) found that Costa Rican butterflies showed no general body size trends with elevation.…”
Section: Body Size Along the Elevational Gradientcontrasting
confidence: 85%
“…Chamberlain et al, ; Nunes et al, ). However, hump‐shaped distributions of dung beetle diversity along elevation have also been observed (Herzog et al, ). For Scarabaeinae dung beetles, we recorded the highest species at 2,260 m ( Onthophagus incantatus ) while the highest Aphodiinae dung beetles were found at 2,770 m ( Bodilus vittifer , Neocolobopterus stefenellii ), patterns which reflect elevational distributions of dung beetles on other African mountains (Davis, Scholtz, & Chown, ; Muhirwa, Maniragaba, Maniragaba, & Kaplin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The factors such as contemporary climate and productivity (Rosenzweig 1995;Fu et al 2007;Rowe 2009;Wang et al 2009;Whittaker 2010;Acharya et al 2011a), evolutionary history (Whittaker 2010;Machac et al 2011), area (Rahbek 1997;Herzog et al 2005;Romdal and Grytnes 2007) and geometric constraints (Colwell et al 2004;McCain 2004;Brehm et al 2007;Rowe 2009) are the most commonly discussed drivers of the elevational diversity gradients. However, the generality of the pattern across taxa and region, and the consensus on underlying mechanisms for the pattern has remained controversial and is much argued and discussed topic in spatial ecology (Oommen and Shanker 2005;Jankowski et al 2012;Sanders and Rahbek 2012;Eisenlohr et al 2013;Herzog et al 2013).…”
Section: Introductionmentioning
confidence: 99%